Development of field-applicable tests for rapid and sensitive detection of Candidatus Phytoplasma oryzae - Wambua, Lillian; Schneider, B.; Okwaro, A.; Wanga, J.O.; Imali, O.; Wambua, P.N.; Agutu, L.; Olds, Cassandra L.; Jones, Christopher S.; Masiga, Daniel K.; Midega, C.A.O.; Khana, Z.; et al. (Elsevier, 2017)
Napier grass Stunt Disease (NSD) is a severe disease of Napier grass (Pennisetum purpureum) in Eastern Africa, caused by the leafhopper-transmitted bacterium Candidatus Phytoplasma oryzae. The pathogen severely impairs the growth of Napier grass, the major fodder for dairy cattle in Eastern Africa. NSD is associated with biomass losses of up to 70% of infected plants. Diagnosis of NSD is done by nested PCR targeting the phytoplasma DNA, which is difficult to perform in developing countries with little infrastructure. We report the development of an easy to use, rapid, sensitive and specific molecular assay for field diagnosis of NSD. The procedure is based on recombinase polymerase amplification and targets the imp gene encoding a pathogen-specific immunodominant membrane protein. Therefore we followed a two-step process. First we developed an isothermal DNA amplification method for real time fluorescence application and then transferred this assay to a lateral flow format. The limit of detection for both procedures was estimated to be 10 organisms. We simplified the template preparation procedure by using freshly squeezed phloem sap from Napier grass. Additionally, we developed a laboratory serological assay with the potential to be converted to a lateral flow assay. Two murine monoclonal antibodies with high affinity and specificity to the immunodominant membrane protein IMP of Candidatus Phytoplasma oryzae were generated. Both antibodies specifically reacted with the denatured or native 17 kDa IMP protein. In dot blot experiments of extracts from infected plant, phytoplasmas were detected in as little as 12,5 μg of fresh plant material.